THE IMPACT OF FIX UP STRATEGY TO IMPROVE READING COMPREHENSION ON THE JUNIOR HIGH SCHOOL SETTING IN INDONESIA - Wahyuni B, Asti; Baharudin, Baharudin; Lufia, Lufia (English Education Department, 2024)
The objective of this research was to find out the impact of fix up strategy to improve reading comprehension on the junior high school setting .This research used quantitative method with quasi-experimental design. The population of this research was all of the seventh-grade students of SMP Negeri 1 Batauga in academic year of 2023/2024. The population consists of 3 classes; VII A, VII B, and VII C. Based on the data obtained from the school, the total population was 89 students. In this study, the researcher used random sampling technique. The sample of this research was (VII A and VII C) two class, there were 30 students as sample. The instrument of this research used multiple choice. The data analyzed by using descriptive statistics analysis. Based on findings in this research, the used fix up strategy to students at SMP Negeri 1 Batauga was in category which was proven by the value of pretest in experimental class which mean score was 43.30 and control class mean score was 37.60. Meanwhile the post-test mean score of experimental class was 71.83 and control class was 57.93. It was obtained that t-count was 5.695 and the t-table 2.010 for alpa (α) 0.05. The t-count was higher than t-table. So that, fix up strategy method effective in improving reading comprehension on descriptive text at SMP Negeri 1 Batauga in academic year 2023/2024.